Small-sided games are not as effective as intermittent running to stimulate aerobic metabolism in prepubertal soccer players - Massamba, A.; Dufour, S. P.; Favret, F.; Hureau, T. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The purpose of this study was to investigate the influence of the soccer pitch area during small-sided games (SSG) in prepubertal children on physiological and technical demands, and to compare them, for the physiological demands, to high-intensity interval training (HIIT). Methods: Ten young soccer players (13.0 [0.3] y) performed a HIIT and 3 SSG of various field sizes (30 × 20 m, 42 × 38 m, and 51 × 34 m). Each SSG was performed with 5 players per team, during 4 × 4-minutes interspaced with 1 minute of passive recovery in between. HIIT also followed a 4 × 4-minute protocol with running speed set on an individual basis. Heart rate (HR) was continuously monitored during training sessions. For each exercise modality, time spent above 90% of HRmax (T=90%,HRmax) was calculated, and technical actions were quantified during SSG by video analysis. Results: T=90%,HRmax was similar between the 3 SSG (~587 [276] s; P > .2) but 24% to 37% lower than during HIIT (826 [140] s, P < .05). Coefficients of variations in T=90%,HRmax were 2.3 to 3.5 times larger in SSG compared with HIIT. For technical actions, greater number of possessions (21 [6] vs ~14 [4]), and lower ball touches per possession (2.4 [0.6] vs ~2.9 [0.6]) were found in the small SSG compared with larger SSG, respectively (P < .05). Conclusion: The 3 SSG led to lower acute stimulation of the aerobic metabolism, suggesting a lower potential for chronic aerobic adaptations, compared with HIIT. Moreover, interindividual variability in the physiological response was substantially greater in SSG compared with HIIT, indicating increased heterogeneity among players performing the same training protocol.